Search strategy for the Evidence review for the project: The future of part-time working: the impact of flexible furlough? - Gascoigne, Charlotte; Kelliher, Clare (Cranfield University, 2021)
Search strategy for the Evidence Review for the ESRC-funded project 'The Coronavirus Job Retention Scheme and employer perceptions of part-time working: the implications for economic recovery and future working'.
Keywords: 'part-time working'; 'flexible working'; 'labour market economics'